NGHIÊN CỨU ẢNH HƯỞNG CỦA CÔNG SUẤT SIÊU ÂM ĐẾN ĐẶC TRƯNG TÍNH CHẤT CỦA VẬT LIỆU KHUNG CƠ KIM MIL-100 - Nguyễn, Thị Phượng; Nguyễn, Thị Hoài Phương; Lê, Thanh Bắc (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDYING THE EFFECT OF ULTRASONIC POWER ON THE PROPERTIES OF MIL-100 METAL FRAME MATERIALSThe metal-organic framework MIL-100 (Fe) was successfully synthesized using the ultrasonic method under different ultrasonic power. The as-synthesized materials were characterized by XRD, SEM, FT-IR and BET. The results showed that these materials have dimensions of a size range of 200-300 nm with similar morphology and structure. Among all the ultrasonic power studied, the material synthesized at ultrasonic power of 1080 W has the largest surface area of 1080.11 m2/g and reaction efficiency of 72.09%.